Morphometric Analysis of Nose of Adult Female (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To determine the mean values of different morphometric measurements from nose of females in study population and to explore the variations in its size and shape.Study: Cross sectional StudyPlace of Study: This study was conducted in the department of ENT Unit – I, Mayo Hospital, Lahore associated with King Edward Medical University, Lahore.Material and Methods: A total of 100 female patients visiting ENT Department, Mayo Hospital, Lahore were randomly selected and recruited for the study. Surface measurements were taken directly from the nose of all subjects included in the study, by inch tape. Each variable was measured twice in centimeters and degrees by the same investigator. Demographic profile and relevant data was recorded in a standard performa. Mean of different morphometric values of nose of female were taken.Results: Mean age of patient was 31.97±12.32 year. Minimum and maximum age was 16 and 60 years. Mean length of dorsum of nose 4.74±0.31cm. Mean nasal width was 3.79±0.28cm. Mean distance between alar crease and tip of nose was 2.43±0.23cm. Mean distance between alar crease and vertical line over upper lip and nasal tip and level of upper lip was 1.00±0.13 and 1.42±0.22cm. Mean nasal root width was 1.41±0.16cm. Naso frontal and naso labial angle was 148.750±6.25 and 109.530±9.35. Mean SM distance was 4.05±0.30cm.
Keywords: Morphometric, Anthropometry, Nose measurements.